2023
DOI: 10.1101/2023.10.31.23296947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meal Effects on Gastric Bioelectrical Activity Utilizing Body Surface Gastric Mapping in Healthy Subjects

I-Hsuan Huang,
Stefan Calder,
Armen A. Gharibans
et al.

Abstract: SummaryBackgroundGastric sensorimotor disorders are prevalent. While gastric emptying measurements are commonly used, they may not fully capture the underlying pathophysiology. Body surface gastric mapping (BSGM) recently emerged to assess gastric sensorimotor dysfunction. This study assessed varying meal size on BSGM responses to inform test use in a wider variety of contexts.MethodsData from multiple healthy cohorts receiving BSGM were pooled, using four different test meals. A standard BSGM protocol was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(93 reference statements)
0
0
0
Order By: Relevance
“…Although the tests were kept as standardized as possible to control for any variability, there was slight variation in the test timings and three participants switched to alternative meals of equal caloric content. However, research has shown no significant differences in the results of EGG 56 or BSGM 57 for calorie-matched meals with different compositions.…”
Section: Discussionmentioning
confidence: 97%
“…Although the tests were kept as standardized as possible to control for any variability, there was slight variation in the test timings and three participants switched to alternative meals of equal caloric content. However, research has shown no significant differences in the results of EGG 56 or BSGM 57 for calorie-matched meals with different compositions.…”
Section: Discussionmentioning
confidence: 97%